New potentials of liner service in maritime trade - Roškar, Edvard (Array, 2007)
Liner shipping, with all its specific features, plays an important role in the economic development of a country whose ports liner ships are calling at. Under classical liner shipping we understand the carriage of cargoes or passengers over long distances and by large vessels. However, it should be considered that a cargo, which has been discharged at the port of destination and has not yet reached the customer, has to be further transhipped onto a road vehicle. Likewise, a road vehicle carries cargo intended for sea transport to a port of shipment. The article aims at presenting a detailed analysis of the weaknesses of the present-day cargo traffic from the shipper to the consignee involving sea and inland transport. It deals with the relation between sea and land transport, favouring the former to the latter. Organizational changes required to abandon the classical transport of cargo are based on the White Paper regarding the European transport policy up to the year 2010